Use of Shock Index, Modified Shock Index, and Age-Adjusted Shock Index for Detection of Postpartum Hemorrhage - Celikkan, Cagla; Ibanoglu, Mujde Can; Engin-Ustun, Yaprak (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Purpose The aim of this study is to evaluate the role of shock index (SI), modified shock index (MSI), and delta shock index (ΔSI) in predicting postpartum hemorrhage (PPH) and adverse maternal outcomes.Material and Methods In this cross-sectional cohort study, a study group consisting of 416 pregnant women who delivered at our hospital and had postpartum hemorrhage was compared with 467 control patients with normal follow-up. SI (pulse/systolic blood pressure), MSI (pulse/mean arterial pressure), ΔSI (input SI – 2nd- or 6th-hour SI) values were calculated.Results A total of 883 postpartum women were included in the study. The study group had higher peripartum, 2nd-hour, and 6th-hour SI values (p=0.011, p=0.001, p<0.001, respectively). Peripartum MSI values (p=0.004), 2nd-hour MSI values (p<0.001), and 6th-hour MSI values (p<0.001) were significantly lower in the control group than in the PPH group. When the groups were evaluated, the cut-off value of the 2nd-hour SI parameter was>0.8909 (sensitivity 30%, specificity 84%), and the 6th-hour SI parameter was>0.8909 (sensitivity 40%, specificity 80%) for predicting postpartum hemorrhage requiring blood transfusion and surgical intervention. The cut-off value of the 2nd-hour MSI parameter was>1.2 (sensitivity 34%, specificity 82%), and the cut-off value of the 6th-hour MSI parameter was>1.2652 (sensitivity 32%, specificity 90%).Conclusion The 2nd- and 6th-hour SI and 2nd- and 6th-hour MSI values were significantly higher in patients with postpartum hemorrhage. Values greater than 0.89 for SI and 1.2 for MSI were considered significant for predicting postpartum hemorrhage with maternal impairment.
Keywords: Diastolic blood pressure; maternal morbidity; mortality; obstetric hemorrhage